Internalisasi Nilai-Nilai Pendidikan Multikultural dalam Membentuk Sikap Toleransi Siswa - Halimah Halimah; Rahma Sita Aulia Fahrida; Ananda Kludia; Ajahari Ajahari (Al-Mau'izhoh: Jurnal Pendidikan Agama Islam, 2026)
This study aims to analyze the internalization of multicultural educational values in shaping students’ attitudes of tolerance within an Islamic educational setting. This study employs a descriptive qualitative approach using library research methods, involving the review of various relevant literature sources such as books, scientific journals, and academic documents. The results of the study indicate that multicultural values from an Islamic perspective, such as tasamuh (tolerance), tawazun (balance), tawassuth (moderation), ta’awun (mutual aid), and ukhuwah (brotherhood), have a strong connection to Islamic teachings and serve as a foundation for the development of students’ attitudes of tolerance. The process of value internalization is carried out multidimensionally through classroom learning, teacher role modeling, an inclusive school culture, extracurricular activities, and daily life practices. This process unfolds through three stages: value transformation, value transaction, and value transinternalization, in which these values are gradually understood, practiced, and become an integral part of students’ character. Additionally, the success of internalization is influenced by supporting factors such as a conducive school environment and teacher competence, as well as inhibiting factors such as the limited availability of cross-cultural activities. The research findings also indicate that the internalization of multicultural values has a significant impact on fostering students’ tolerant attitudes, such as openness, respect for differences, the ability to collaborate, and empathy. Thus, multicultural education plays a crucial role in fostering social harmony amid diversity. However, this study is limited to a literature review; therefore, further research is recommended to adopt an empirical approach to yield more comprehensive results.